2020
DOI: 10.1111/cge.13888
|View full text |Cite
|
Sign up to set email alerts
|

Selective forces acting on spinocerebellar ataxia type 3/Machado–Joseph disease recurrency: A systematic review and meta‐analysis

Abstract: Spinocerebellar ataxia type 3/Machado–Joseph disease (SCA3/MJD) is a dominant neurodegenerative disease caused by the expansion of a CAG repeat tract in ATXN3. Anticipation and worsening of clinical picture in subsequent generations were repeatedly reported, but there is no indication that SCA3/MJD frequency is changing. Thus, we performed a systematic review and meta‐analysis on phenomena with potential effect on SCA3/MJD recurrency in populations: instability of CAG repeat transmissions, anticipation, fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Recruitment biases were not clearly avoided in studies on instability and anticipation in SCA2, as observed previously in SCA3/MJD 61 . However, it is important to note that the main recruitment problems would tend to operate in opposite directions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recruitment biases were not clearly avoided in studies on instability and anticipation in SCA2, as observed previously in SCA3/MJD 61 . However, it is important to note that the main recruitment problems would tend to operate in opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…We have followed, on purpose, the same approach as the systematic review carried out on another polyQ ataxia, SCA3/MJD 61 . Our intention was to compare the evolutionary destinies of different polyQ diseases by following the same systematic questions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation is typically expanded when passed to the next generation. Known as an 'anticipation effect,' this phenomenon results in more severe symptoms manifesting 8–10 years earlier in each subsequent generation( Sena et al, 2021 ). Multiple generations may be affected concurrently, profoundly impacting caregivers, who may also be affected or at risk of MJD ( Carr et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%